ANALYSIS OF INSURERS ON THE LIFE INSURANCE MARKET IN UKRAINE - Melnichyk , Yu.M. (The actual problems of regional economy development, 2016)
This article is analyzed to the analysis of life insurance market in Ukraine. The study is an analysis of the financial condition of insurers leaders of term life insurance. The article examines the performance of insurers, analyzes the financial condition of companies. The conclusions on the state of the insurer's life insurance market are made. The study used a set of general and specific methods which are interrelated and used to work in a logical and consistent communication. The conclusions are made and suggestions for improving the financial condition of insurers to improve life insurance in the modern insurance market of Ukraine are offered. JEL: G 22